Analisis Permainan Cur-Cur Pal untuk Meningkatkan Kemampuan Sosial Emosional Anak - Mita Sari; Salsa Aprilla Patilima; Siti Nur Azkiah I. Hulawa; Sri Putri Enjelita; Nahara R. Yamudu; Fizria R. Dai (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The aim is to assess the effectiveness of traditional hide and seek games in early childhood and elementary school. This study utilizes literature research methods. Play is essential for children, as every child desires to play continuously because it helps them relax and alleviate stress. There are numerous games played outside the home that can enhance children's social and emotional development, such as traditional games like hide and seek. Character values embedded in the traditional game of hide and seek include: a) Religious. Religious values are evident when children pray together before playing. b) Sport sman ship and Honesty. Sport sman shipis demons trate dwhen player sad heret oth eagreed - uponrules and exhibit honesty while being guards. c) Love for the Motherland. Preserving Indonesian culture showcases children's love for the Republic of Indonesia. d) Being friendly/communicative. Communication during a game is crucial to avoid misunderstandings among players. e) Accuracy. Players need to be accurate in finding hiding spots that are challenging for the guards to discover and in determining the rightmomenttotouchthebase.f)Independence and diligencein the game ofhideand seek. g)Democratic. Democratic values are evident when players show respect and consideration for each other despite their differences. h) Responsibility. The value of responsibility is demonstrated by players searching for hiding spots and guards being prepared to find their friends and protect the base. i) Compliance. The value of compliance is observed when all players agree to certain rules before commencing the game